The impossible self-portrait - Piotr Śliwiński (Przestrzenie Teorii, 2014)
This sketch deals with Różewicz’s feeling that identity issues are unresolvable. This feeling, which became increasingly strong in the poet’s later works, led him to lose control over poetic form and employ more rhetoric as well as caused his works to be similar to performing arts. A description of the similarities between Różewicz’s cultural ideas and the ones that are present in popular rock music is an important part of this article.